2020
DOI: 10.30892/gtg.28115-462
|View full text |Cite
|
Sign up to set email alerts
|

From Satisfaction in Eco-Tourism to Loyalty in a National Park

Abstract: Ge eo oJ Jo ou ur rn na al l o of f T To ou ur ri is sm m a an nd d G Ge eo os si it te es s Year X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
(61 reference statements)
2
10
0
Order By: Relevance
“…Thus, environmental responsibility in tourism refers to responsible travel, which is especially carried out towards some natural protected conservation areas . Recent studies have researched the ecotourism potential and zoning, nature protection and sustainable tourism interaction as well as residents' perceptions towards protected areas and ecotourism (Balist et al, 2019;Carvache-Franco et al, 2018;Carvache-Franco et al, 2020;Jojić et al, 2018;Šiljeg et al, 2019;Stojanović et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, environmental responsibility in tourism refers to responsible travel, which is especially carried out towards some natural protected conservation areas . Recent studies have researched the ecotourism potential and zoning, nature protection and sustainable tourism interaction as well as residents' perceptions towards protected areas and ecotourism (Balist et al, 2019;Carvache-Franco et al, 2018;Carvache-Franco et al, 2020;Jojić et al, 2018;Šiljeg et al, 2019;Stojanović et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, ecological and nature experiences, signboards, and accessibility, which are found in general parks [16][17][18], were rated relatively highly in GLP, indicating that GLP is not just regarded as a simple park. On the other hand, the ratings were lower for nearby eateries, entertainment inside and outside the park, and interpretations, unlike for tourism destinations [11,12,14,15] and ecotourism sites [35,[54][55][56]. This suggests that, although the park has attributes as an overall leisure and tourism destination, more effort is needed to raise its level.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas various entertainment and experience activities are emphasized at general tourism sites, experiential activities that can be performed with natural resources (e.g., authentic interactions with nature, activities with live animal) and waterside experiences (e.g., canoeing, fishing, kayaking) are emphasized at ecotourism sites [25,35]. Interpretation conveys knowledge and increases visitors' eco-friendly behaviors [54][55][56]. Given that various studies are being conducted on interpretation design and training, and given the relation between interpretation and satisfaction, it is evident that interpretation is a major attribute of ecotourism sites [34,57].…”
Section: Destination Attributes Of Parks Tourism Destinations and Eco...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ivyanno (2013) suggested that if tourists are satisfied with the activities and the service quality of the tourist site, they tend to recommend it to their friends and relatives. Thereby, satisfaction has a positive impact on word-of-mouth intention, which is an essential factor to attract tourists (Carvache-Franco et al, 2020;Hossain et al, 2021). Therefore, the following hypothesis is stated:…”
Section: Satisfaction With the Destination Effects Word-of-mouth Intentionmentioning
confidence: 98%